Weakened large-scale surface heat flux feedback at midlatitudes under global warming - Zhiqiao Wang; Zhao Jing; Fengfei Song (Nature Communications)
Abstract The surface heat flux feedback, which refers to the response of surface heat flux anomaly to the underlying sea surface temperature anomaly (SSTA), is one of the key processes in air-sea interaction. It plays an important role in regulating various aspects of the climate system, ranging from local SSTA persistence to the global overturning circulation and major climate modes. Yet its change under greenhouse gas-induced warming remains unknown. Here, using an ensemble of global climate simulations under a high radiative forcing scenario, we demonstrate that the intensity of surface heat flux feedback for spatially large-scale SSTA at the midlatitudes is projected to halve by the end of the 21st century, compared to pre-industrial levels. Such weakening is primarily attributed to a more stabilized marine atmospheric boundary layer, which diminishes the air-sea thermal disequilibrium caused by SSTA. In a warming climate, the variance of midlatitude SSTA at large spatial scales is expected to be significantly enhanced in response to the weakened surface heat flux feedback.